The Role of Authoritarian Parenting Style and Academic Resilience in Shaping Scholarship Students' Confidence in Career Decision-Making - Melati Resda Ceasaria; Stefani Virlia (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
This study analyzes the role of academic resilience and authoritarian parenting style in shaping Career Decision-Making Self-Efficacy (CDMSE) among scholarship recipients. A quantitative approach with a correlational design was used, with participants selected through purposive sampling. Data were collected using questionnaires measuring academic resilience, authoritarian parenting style, and CDMSE, then analyzed using regression analysis. The results show that academic resilience positively contributes to CDMSE, helping students overcome academic challenges and increasing their confidence in making career decisions. Authoritarian parenting style has an ambivalent impact, fostering discipline while also increasing psychological pressure that may hinder career exploration. The implications of this study highlight the importance of psychological interventions in academic settings to strengthen academic resilience and the need for a more balanced parenting approach to provide students with the flexibility to pursue career paths that align with their interests and competencies.Penelitian ini menganalisis peran academic resilience dan authoritarian parenting style dalam membentuk Career Decision-Making Self-Efficacy (CDMSE) pada mahasiswa penerima beasiswa. Pendekatan kuantitatif dengan desain korelasional digunakan dalam penelitian ini dengan partisipan yang dipilih melalui teknik purposive sampling. Data dikumpulkan menggunakan kuesioner yang mengukur academic resilience, authoritarian parenting style, dan CDMSE kemudian dianalisis menggunakan analisis regresi. Hasil penelitian menunjukkan academic resilience berkontribusi positif terhadap CDMSE membantu mahasiswa menghadapi tantangan akademik dan meningkatkan kepercayaan diri dalam mengambil keputusan karir. Authoritarian parenting style memiliki dampak ambivalen di satu sisi membentuk kedisiplinan tetapi juga meningkatkan tekanan psikologis yang dapat menghambat eksplorasi karir. Implikasi penelitian ini menyoroti pentingnya intervensi psikologis di lingkungan akademik untuk memperkuat academic resilience serta perlunya pendekatan pola asuh yang lebih seimbang agar mahasiswa memiliki fleksibilitas dalam menentukan jalur karir sesuai dengan minat dan kompetensinya.